2022
DOI: 10.29312/remexca.v13i28.3281
|View full text |Cite
|
Sign up to set email alerts
|

Producción de maíz forrajero con dos sistemas de riego y tres niveles de la evaporación aplicada

Abstract: La eficiencia en el uso del agua para la producción de forraje agrupa una serie de componentes relacionados con el cultivo y el sistema de riego que consiste en obtener una mayor producción por unidad de agua consumida. El objetivo del trabajo fue conocer el rendimiento, calidad nutricional y la eficiencia en el uso del agua (EUA) del cultivo del maíz forrajero (Zea mays L.) en dos sistemas de riego bajo tres niveles de evaporación aplicada. El trabajo se estableció el 19 de abril de 2019, en el Campo Experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
0
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 10 publications
2
0
1
1
Order By: Relevance
“…Similar results to those in this study (Table 2) were found by Zaragoza-Esparza et al (2019), lower than those obtained by Gutiérrez-Guzmán et al (2022), who reported higher percentages of ADF and NDF ranging from 30.4 to 36.8, and 51.27 to 60.53%, respectively, in forage maize production in the Lagunera Region.…”
Section: Nutritional Qualitysupporting
confidence: 91%
See 2 more Smart Citations
“…Similar results to those in this study (Table 2) were found by Zaragoza-Esparza et al (2019), lower than those obtained by Gutiérrez-Guzmán et al (2022), who reported higher percentages of ADF and NDF ranging from 30.4 to 36.8, and 51.27 to 60.53%, respectively, in forage maize production in the Lagunera Region.…”
Section: Nutritional Qualitysupporting
confidence: 91%
“…Regarding net lactation energy (NLE), the highest values were found in the treatment with drip-tape irrigation depth at 0.05 m (1.59 Mcal kg 1 ), while in the treatments of 0.15 and 0.30 m depth, lower values were obtained (1.55 Mcal kg 1 ). This is due to the fact that they obtained greater fiber production, therefore, the energy value was negatively associated with those concentrations, which in turn had an impact on the production of NLE (Gutiérrez-Guzmán et al, 2022). The NLE results of this study are superior to those reported by Yescas et al (2015), who obtained concentrations of 1.36 and 1.08 Mcal kg 1 of NLE in their quality evaluation of forage maize at different levels of subsurface drip irrigation.…”
Section: Nutritional Qualitycontrasting
confidence: 77%
See 1 more Smart Citation
“…En el mundo, más del 70 % de las extracciones de agua dulce o potable, están relacionadas con el sector agrícola (1) , y en México es el 76 %. Parte de esto, aproximadamente el 29 % se utiliza para el crecimiento de cultivos forrajeros (2) , una de las especies más cultivadas es el maíz forrajero por el alto valor energético que aporta al ganado (3) cuya función es generar proteínas para el consumo humano. El contenido de proteínas puede considerarse una unidad de medida valiosa para comparar alimentos (4) .…”
Section: Introductionunclassified